Promjena etničke strukture opština u Bosni i Hercegovini prema popisu stanovništva iz 2013. godine / Ethnic Structure Changes in B-H Municipalities According to the Census of 2013. - Pejanović, Mirko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
In a research study on the ethnic structure of municipalities in Bosnia and Herzegovina, according to the Census 1991 and 2013 the changes in the demographic structure of the population that occurred from 1991 to 2013 are elaborated. Special attention is given to changes in the ethnic structure of the population according to Census 2013. The observation unit of monitoring changes in the population ethnic structure are municipalities as basic territorial self-government unit in which inhabitants of a country live. Comparison of municipalities’ ethnic structure after the 1991 Census with the ethnic structure of the Census 2013 showed that there were radical changes in the ethnic structure in the BH municipalities. According to the census for Bosnia and Herzegovina in 2013, two-thirds of the municipalities have a mono-national structure in percentage ranging from 70% to 99%. Such changes in ethnic structure are caused by the violent ethnic cleansing policies during the war and the prevailing influence of ethnic parties in the exercise of power in the postwar period. The ethnic homogenization of the population recorded in the 1992-1995 war takes place peacefully as ethnic territorialisation. The ethnic territorialisation space has its basis in the ethno-politics mono-ethnic parties. Due to such movement at the BH social area, the forming of ethnic territorialization areas is completed. It takes place in the form of Republic of Srpska for the Serbs, then in the form of five cantons for Bosniaks: Tuzla, Una-Sana, Sarajevo, Zenica-Doboj and Bosnia-Podrinje. The ethnic territorialized space for Croatian people is Zapadna Herzegovina, Hercegbosanski and Posavina Canton. Multi-ethnic structure of the population has been preserved place in the city of Mostar, Brčko District and municipalities: Jajce, Bosanski Petrovac, Vukosavlje, Lake, Donji Ţabar, Gornji Vakuf, Pelagićevo, Žepče and Busovača.